Rational expectations: Retrospect and prospect - Kevin Hoover; Warren Young (Duke University, Center for the History of Political Economy (CHOPE), 2011)
The transcript of a panel discussion marking the fiftieth anniversary of John Muth's "Rational Expectations and the Theory of Price Movements" (Econometrica 1961). The panel consists of Michael Lovell, Robert Lucas, Dale Mortensen, Robert Shiller, and Neil Wallace. The discussion is moderated by Kevin Hoover and Warren Young. The panel touches on a wide variety of issues related to the rational-expectations hypothesis, including: its history, starting with Muth's work at Carnegie Tech; its methodological role; applications to policy; its relationship to behavioral economics; its role in the recent financial crisis; and its likely future.
Keywords: B22; B31; B26; E17; 330; rational expectations; John F. Muth; macroeconomics; dynamics; macroeconomic policy; behavioral economics; efficient markets